If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-138 > -6 (6b-7) =0
We simplify the equation to the form, which is simple to understand
-138>-6(6b-7)=0
Reorder the terms in parentheses
+(-828b+966)=0
Remove unnecessary parentheses
-828b+966=0
We move all terms containing b to the left and all other terms to the right.
-828b=0-966
We simplify left and right side of the equation.
-828b=-966
We divide both sides of the equation by -828 to get b.
b=1.1666666666667
| 2n-1=-11 | | 4x+8y=52 | | 3n-8=-20 | | 4x-10=12+4(x+8) | | 2-c=29 | | ?(2x-4)=-?(x+1) | | 4t-1=5(t+5) | | 3x=7x+20 | | 5(6+3r)+7127= | | 13mn-5nm+2mn= | | 6+5ln(2x-1)=21 | | 2x+14=8-3y | | x^2-15x+(56.25)=8 | | 1.6=2y+7.8 | | 4-n=6 | | 5=25/d | | 8x-15x-6=40 | | 7.5r+2=-284 | | 7(5x-10)=4(4x-8) | | 8-1(3x+4)=6x | | 20+3z=-4 | | -.6=-.3u | | 3x^2+0x-42=0 | | x^2=2-x | | px-p^2+5x+25=0 | | (8x+7)(7x+8)=0 | | 4Z=4.8 | | (3x-4)(8x+2)=0 | | 7a+4b-3a-b= | | 8+5n=-2 | | -3W=24 | | 9x=2x+44 |